Moths of Western North America 1. Distribution of Saturniidae of Western North America - Opler, Paul A., author; Peigler, Richard S., author; C.P. Gillette Museum of Arthropod Diversity, publisher (Colorado State University. Libraries, 1993)
This is the first number of a series of atlases detailing the distributional occurrence of the moths of North America. The atlas of Saturniidae by Richard Peigler and me covers the documented distribution of a well-known group.
Distribution of Saturniidae of Western North America
Keywords: Saturniidae -- West (U.S.) -- Geographical distribution; Saturniidae -- Canada, Western -- Geographical distribution; Saturniidae -- Mexico, North -- Geographical distribution; Saturniidae -- West (U.S.) -- Maps; Saturniidae -- Canada, Western -- Maps; Saturniidae -- Mexico, North -- Maps